Developing Managerial Framework to Cultivate Critical Skills in The South African Automotive Retail Industry - Sirayi, Siyabonga; Msuthwana, Vusumzi; Mazibuko, Noxolo (GILE Journal of Skills Development, 2024)
The purpose of this study is to develop managerial framework that could be utilised to cultivate critical skills in the automotive retail industry. This would be achieved by providing a comprehensive literature overview regarding skills development strategies including life-long learning, apprenticeship, and mentorship programmes. The study utilised a qualitative research methodology. Data are collected through face-to-face interviews using an interrogation technique. Data collection process was done in participants’ natural settings, enabling the researcher to develop new knowledge, and understanding of strategic tools that can be utilised to promote skills development of technicians for the automotive retail industry. The findings reveal a strong collaboration between non-technical and technical high schools as well as technical colleges is essential to ensure the quality of skills development in the automotive retail industry is improved, and thereby improve the market pool of skilled young technicians.